Analysis of the Implementation of the Merdeka Belajar Curriculum at SMAN 1 Taliwang - tanasa, lala novela; Ningsih, Andi; Siti Masitah, Baiq; kamaluddin, kamaluddin; Afian, Tilal (JUPE : Jurnal Pendidikan Mandala, 2023)
This research aims to identify and collect information about the implementation of the Merdeka Belajar Curriculum at SMAN 1 Taliwang. The method used in this research is a qualitative descriptive method that aims to explain the subject's situation and data obtained during observations and interviews so as to produce information that readers can understand about the independent curriculum implemented at SMAN 1 Taliwang. The data analysis technique consists of three stages, namely data reduction, data presentation, and conclusion. The research results show that the implementation of the independent curriculum at SMAN 1 Taliwang is running optimally. However, attention is still needed to meet the availability of facilities and infrastructure, but overall, the learning process is running well.